Pengujian Black Box Pada Aplikasi Database Perguruan Tinggi dengan Teknik Equivalence Partition - Raihan, Hamzah; Voutama, Apriade (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
In this digital era, the development of information technology increasingly offers various types of innovations aimed at the convenience of every user. The university database application is an application that is used to manage student data, faculties, courses, majors and student grades. There are 2 application testing methods, namely white box testing and black box testing. For testing this software will be tested using the black box method with the equivalence point technique. Black Box testing does not require source code. Equivalent partitioning is a test method based on the performance of input data in a performance data application system, where each input menu is tested and also grouped according to its function, valid or not. The purpose of this method is to detect application errors so that they can be fixed more quickly. The test results contained 35 test cases from the university database application and 4 test cases obtained were not as expected. Although there are 31 successful test cases, there are things that need to be improved from the output generated by the application